Elevated Rest Heart Rate in Psychiatric Patients and Different Effects of Psychotropic Medication - Sarlon, J.; Habich, O.; Schneider, B. (Pharmacopsychiatry, 2016)
Introduction: Elevated rest heart rate (RHR) is a known risk factor of cardiovascular diseases. The aim of this study was to analyse the effects of different psychiatric disorders and psychotropic medication on RHR.Methods: In this retrospective study, medical records of 590 inpatients with a psychiatric disorder (309 men, 281 women, mean age 42.11; SD=13.8 years) were evaluated. RHR, the psychiatric diagnosis according to ICD-10, the psychotropic medication and the use of beta blockers were assessed.Results: The average RHR of all patients was 85.62 beats per minute (bpm) (SD=10.60 bpm) which is, according to the literature and the consensus of experts, to be considered as a relevant elevation of RHR. There was a significant negative correlation between age and RHR. Patients treated with monotherapy or with SSRI showed in the multiple regression analysis significant lower RHR than other subjects, whereas both polytherapy with more antipsychotics and the diagnosis of schizophrenia could be identified as an independent risk factor of elevated RHR (p<0.05, 2-tailed). The presence of hypertonia, diabetes, hypercholesterolemia or obesity has no influence on RHR. 6% of the study population received beta blocker during the hospitalization.Discussion: The elevated RHR in psychiatric patients is a common phenomenon and can be observed independently of the use of psychotropic medication but more in patients with schizophrenia. An interesting additional finding could be a possible protective effect of SSRI on RHR in psychiatric patients.
Keywords: antipsychotic drugs; schizophrenia; selective serotonin reuptake inhibitors; (SSRIs); stress